Study of ER PR receptors in breast carcinoma: a study of 30 cases - Patel, Himanshu R.; Shrimal, Ankur; Trivedi, Harsh P. (International Surgery Journal, 2018)
Background: Estrogen and Progesterone receptors are found in breast cancer cells that depend on estrogen and related hormones to grow. These are steroidal nuclear type of receptors. The most common method currently used to test a tumor for estrogen and progesterone receptors is immunohistochemistry or IHC. Patients with positive hormone receptor cancer have better survival. They are candidates of anti-hormonal therapy. Methods: This is a retrospective study was carried out in the Department of Surgery of a tertiary care hospital, affiliated to Government Medical College. This is a retrospective study in which 30 randomly selected case records of breast cancer patients, who presented in the period between 2011 to 2016, and who had undergone surgery, were taken and studied in terms of history, examination, investigations, treatment given, histopathology report and development of recurrence, metastasis and survival. Results: In this study out of 30 patients, 25 patients received adjuvant chemotherapy. 2 patients developed recurrence at local site.1 patient was ER/PR both negative and 1 patient was ER +/PR-. 3 patients developed metastasis. Among these, 2 patients were ER/PR both negative and 1 patient was having ER/PR both positive. Conclusions: Hormone receptors play a significant role in breast carcinoma. Breast cancer is more common in postmenopausal group as compared to premenopausal group. Mean age at diagnosis of breast cancer in western countries is 61 years and in India it is 50 years.